Robust Control of a Quadcopter Flying via Sliding Mode - Rudi Uswarman; Swadexi Istiqphara; Rajif Agung Yunmar; Arkham Zahri Rakhman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Sliding Mode Control (SMC) used to control the stability of a quadcopter from disturbances and uncertainties. This technique has two main advantages: the nonlinear dynamics and modelling errors of the quadcopter can be eliminated by switching function and the uncertainty problem can be overcome with a closed-loop response. The controller of the sliding mode technique consists of two components. The first is design equivalent control law to maintain the system state trajectory on the sliding surface. The second is design switching control law to reach the sliding surface. The Lyapunov theorem is used to ensure the stability of the system. Simulation results verify the robustness of the controller.